Parametric Architectural Design for a New City Identity: Materials, Environments and New Applications - Inès Sahtout Gaha (Alanya Üniversitesi, 2023)
In contemporary architectural Design, we speak of a parametric structural design. A design that integrates new functionalities crossed with the spatial geometry of objects. It has been considered structured because it optimizes combinations that integrate a minimum of materials and data to respond to functions, uses, and needs more adapted to a society in perpetual evolution. Parametric modelling allows the usability of new materials and the integration of new structures in a variety of design environments. This transdisciplinary research explores aspects of parametric modelling, a design method that creates digital models using algorithms and parameters. By focusing on the material and immaterial plurality of the designed space, this method enables the generation of complex and innovative forms that would be difficult to realize with traditional methods. Then, from a position that redefines the city as both a